Two-dimensional lamellar structure CuO and preparation method and application thereof

The two-dimensional sheet structure CuO was prepared by hydrothermal reaction and pyrolysis oxidation methods, and its crystal surface structure was regulated, which solved the problem of low selectivity of C2+ products in electrocatalysis of existing Cu oxides, and achieved efficient ethylene generation.

CN119660781AActive Publication Date: 2025-03-21NINGXIA UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411892127.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing Cu oxides have low selectivity for C2+ products during electrocatalysis, making it difficult to effectively convert carbon dioxide into ethylene.

Method used

The two-dimensional lamellar structure CuO was prepared by hydrothermal reaction, and the crystal surface structure of CuO was adjusted by in-situ synthesis method, and the crystal surface selectivity of CuO was optimized by pyrolysis and oxidation method.

Benefits of technology

The high selectivity of CuO for ethylene in electrocatalytic CO2 reduction reaction is achieved, the generation efficiency of C2+ products is improved, and the generation of CH4 is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660781A_ABST
    Figure CN119660781A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalytic carbon dioxide reduction reaction, and discloses CuO with a two-dimensional lamellar structure as well as a preparation method and application thereof. The preparation method of the CuO with the two-dimensional lamellar structure comprises the following steps: mixing terephthalic acid, a first organic solvent, a second organic solvent and Cu (NO3) 2.3 H2O, and carrying out hydrothermal reaction to obtain Cu-MOF; and calcining the Cu-MOF to obtain the CuO with the two-dimensional lamellar structure. According to the preparation method, Cu-MOF of a two-dimensional lamellar stacked nano-structure is prepared by an in-situ synthesis method, the Cu-MOF of the two-dimensional lamellar stacked nano-structure is taken as a precursor, the crystal face of the two-dimensional lamellar CuO material is regulated and controlled by a simple pyrolysis oxidation method, and accurate regulation and control on the preferential selectivity of the CuO crystal face can be realized by controlling the pyrolysis temperature, so that high selectivity of CO2RR on ethylene is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic carbon dioxide reduction reaction, and in particular to a two-dimensional layer structure CuO and a preparation method and application thereof. Background Art

[0002] Electrocatalytic conversion of carbon dioxide (CO2) into high-value-added chemicals and fuels is a promising technological approach to transform waste into valuable resources and promote the development of a sustainable society. 2+ The products have attracted much attention due to their high value, especially ethylene, which is an important component of the chemical industry and has become the focus of this field. However, the efficient conversion of CO2 into ethylene remains a daunting challenge. It is worth noting that copper-based catalysts in the field of transition metal catalysts have excellent C 2+ Generally speaking, the electrocatalytic CO2 reduction reaction (CO2RR) on copper-based catalysts consists of three key steps: efficient CO2 diffusion to the catalyst interface, activation of CO2 molecules at the interface, coordinated proton-electron transfer (CPET) step, and finally the formation of * Finally, the catalyst must have high activity in promoting the CC coupling reaction to promote the C 2+ The formation of products.

[0003] To overcome its limitations, researchers have developed some effective strategies, such as developing efficient electrocatalysts, regulating the electrode-electrolyte interface, and optimizing the electrolyzer design. However, CC coupling is the key factor determining the performance of various C 2+ The most critical step for product selectivity and yield. In addition, there is still a lack of comprehensive consensus on the CC coupling mechanism. In addition, to promote CC coupling on copper surfaces, strategies such as morphology tuning, crystal face regulation, chemical state manipulation, and surface modification have become research hotspots, among which the crystal face is considered to be a key parameter. From the perspective of the crystal structure of copper, Cu(100) with a lower surface coordination number has higher CO dimerization reaction activity and C 2+ Product selectivity. Theoretical calculations show that the two * CC coupling of CO intermediates favors the production of ethylene. Therefore, controlling the exposure of Cu(100) is considered necessary to promote ethylene selectivity. However, the dynamic reconstruction of copper crystal faces during CO2RR is driven by its low condensation energy, and maintaining the crystal structure is a challenge, which is exacerbated by CO2RR intermediates. Therefore, it is necessary to ensure the stability of the Cu(100) crystal surface during the CO2RR reaction while increasing the Cu(100) content in the catalyst material.

[0004] CuOx ), which has attracted much attention due to its broad chemical selectivity for a variety of multi-carbon products. Studies have reported that copper oxide-derived copper surfaces have more grain boundary defects, which are active sites for CO2RR, thereby improving its activity; while some people believe that the increased activity may be purely due to the increase in active sites due to the rougher morphology. CuO x It is reduced to copper in the reaction, and is more inclined to produce C 2+ Compared with the in-situ oxidation method, electrodeposition method and hydrothermal method, the copper oxide obtained by the thermal oxidation method in air is thicker and rougher, and has high activity at low overpotential, while high overpotential leads to severe mass transfer limitation due to high current density, resulting in C 2+ The product selectivity is lower than other methods.

[0005] Therefore, how to improve the performance of Cu oxides in electrocatalytic processes 2+ Product selectivity is an issue that needs to be addressed urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a two-dimensional layered structure CuO and its preparation method and application, so as to solve the problem that the existing Cu oxide has a poor electrocatalytic effect on C 2+ The problem of low product selectivity.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a two-dimensional layered CuO structure, comprising the following steps:

[0009] The terephthalic acid, the first organic solvent, the second organic solvent and Cu(NO3)2·3H2O are mixed and subjected to a hydrothermal reaction to obtain Cu-MOF;

[0010] Cu-MOF is calcined to obtain two-dimensional layered structure CuO.

[0011] Preferably, in the above-mentioned method for preparing a two-dimensional lamellar structure CuO, the usage ratio of the terephthalic acid, the first organic solvent, and the second organic solvent is 30-50 mg: 1-6 mL: 0.5-3 mL;

[0012] The first organic solvent is N,N-dimethylformamide or dimethyl sulfoxide;

[0013] The second organic solvent is ethanol, methanol, propanol or isopropanol.

[0014] Preferably, in the above-mentioned method for preparing a two-dimensional lamellar structure CuO, the mass ratio of terephthalic acid to Cu(NO3)2·3H2O is 3-5:2-4.

[0015] Preferably, in the above method for preparing a two-dimensional lamellar structure CuO, the temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 4-8 hours.

[0016] Preferably, in the above-mentioned method for preparing a two-dimensional lamellar structure CuO, the calcination conditions are: the initial temperature is 20-30°C, the final temperature is 200-800°C, the heating rate to the final temperature is 1-5°C / min, and the holding time at the final temperature is 1-5h.

[0017] The invention also provides a two-dimensional lamella structure CuO prepared by a preparation method of the two-dimensional lamella structure CuO.

[0018] The present invention also provides an application of two-dimensional sheet structure CuO in electrocatalytic CO2 reduction to produce ethylene.

[0019] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention is different from single CuO x Nanoparticle structure, using an in-situ synthesis method to prepare a two-dimensional layer stacking nanostructured Cu-MOF, it was found that during the direct pyrolysis process, the two-dimensional layer stacking nanostructure had a crystal plane control effect, using the two-dimensional layer stacking nanostructured Cu-MOF as a precursor, and regulating the crystal plane of the two-dimensional (2D) layer CuO material through a simple pyrolysis oxidation method. By controlling the pyrolysis temperature, the CuO crystal plane preferential selectivity can be precisely controlled, which is different from one-dimensional nanoparticles / nanowires and other structures, achieving high selectivity for ethylene in CO2RR. Due to the 2D layer structure, during the pyrolysis process, CuO crystals have a crystal plane preferential selectivity. Therefore, during the transformation process in which CuO is reduced to copper in the reaction, it also has preferential conversion characteristics for the copper crystal plane, achieving high selectivity for ethylene. This is consistent with the unstable and complex Cu + / Cu 0 Compared with the ratio / crystal surface control strategy, the pyrolysis oxidation method of the present invention controls the 2D CuO crystal surface with good stability and easy control, thereby enhancing the CO2RR activity and providing CuO x The preparation of electrodes provides a new approach to achieve high selectivity for ethylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0022] Figure 1 XRD patterns of the two-dimensional (2D) lamellar structure CuO in Examples 1 to 6 and the Cu-MOF in Example 1;

[0023] Figure 2 is the SEM image of Cu-MOF in Example 1;

[0024] Figure 3 is the SEM image of the two-dimensional (2D) lamellar structure CuO in Examples 1 to 6;

[0025] Figure 4 This is the CO2RR performance diagram of the two-dimensional (2D) lamellar structure CuO in Examples 2 to 6. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a two-dimensional layered CuO structure, comprising the following steps:

[0027] The terephthalic acid, the first organic solvent, the second organic solvent and Cu(NO3)2·3H2O are mixed and subjected to a hydrothermal reaction to obtain Cu-MOF;

[0028] Cu-MOF is calcined to obtain two-dimensional layered structure CuO.

[0029] In the present invention, the usage ratio of terephthalic acid, the first organic solvent and the second organic solvent is preferably 30-50 mg: 1-6 mL: 0.5-3 mL, more preferably 35-45 mg: 2-5 mL: 0.8-2.5 mL, and more preferably 38-41.5 mg: 3-4.5 mL: 1-2 mL.

[0030] In the present invention, the first organic solvent is preferably N,N-dimethylformamide or dimethyl sulfoxide, and more preferably N,N-dimethylformamide.

[0031] In the present invention, the second organic solvent is preferably ethanol, methanol, propanol or isopropanol, more preferably ethanol, propanol or isopropanol, and more preferably ethanol.

[0032] In the present invention, the mass ratio of terephthalic acid to Cu(NO3)2·3H2O is preferably 3-5:2-4, more preferably 3.5-4.5:2.5-3.5, and more preferably 3.8-4.15:2.8-3.02.

[0033] In the present invention, the specific process of the mixing is:

[0034] Terephthalic acid was added to a mixed solution of N,N-dimethylformamide and ethanol, and magnetic stirring was performed until the terephthalic acid was dissolved. Then, Cu(NO3)2·3H2O was added, and magnetic stirring was performed for 10 minutes, followed by ultrasonication until the Cu(NO3)2·3H2O was dissolved.

[0035] In the present invention, the temperature of the hydrothermal reaction is preferably 100-200°C, more preferably 125-176°C, more preferably 130-150°C; the time of the hydrothermal reaction is preferably 4-8h, more preferably 4.5-7.5h, more preferably 5-6h.

[0036] In the present invention, after the hydrothermal reaction is completed, the method further comprises: washing the obtained product with ethanol, centrifuging, and drying the precipitate obtained by centrifugation;

[0037] The drying temperature is preferably 50 to 70° C., more preferably 55 to 65° C., and more preferably 58 to 60° C.; the drying time is preferably 6 to 12 hours, more preferably 7 to 10 hours, and more preferably 8 to 9 hours.

[0038] In the present invention, the calcination conditions are as follows: the initial temperature is preferably 20-30°C, more preferably 21-27°C, and more preferably 23-25°C; the final temperature is preferably 200-800°C, more preferably 400-700°C, and more preferably 500-600°C; the heating rate to the final temperature is preferably 1-5°C / min, more preferably 1.5-4.5°C / min, and more preferably 2-4°C / min; the holding time at the final temperature is preferably 1-5h, more preferably 1.5-4.5h, and more preferably 2-3h.

[0039] In the present invention, after the calcination is completed, it also includes naturally cooling to room temperature.

[0040] The invention also provides a two-dimensional lamella structure CuO prepared by a preparation method of the two-dimensional lamella structure CuO.

[0041] The present invention also provides an application of two-dimensional sheet structure CuO in electrocatalytic CO2 reduction to produce ethylene.

[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] A method for preparing a two-dimensional layered CuO structure comprises the following steps:

[0045] 830 mg of terephthalic acid was added to a mixed solution formed by 45 mL of N,N-dimethylformamide and 20 mL of ethanol, and magnetic stirring was performed until the terephthalic acid was dissolved; 604 mg of Cu(NO3)2·3H2O was added, and magnetic stirring was performed for 10 min, followed by ultrasonication until the Cu(NO3)2·3H2O was dissolved; the mixture was transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at 150°C for 6 h, the obtained product was washed with ethanol, centrifuged, and the precipitate obtained by centrifugation was placed in a forced air drying oven and dried at 60°C for 8 h to obtain Cu-MOF;

[0046] The Cu-MOF was placed in a muffle furnace and heated from 25°C to 200°C at a heating rate of 2°C / min, and kept at 200°C for 2 hours. After the insulation, it was naturally cooled to room temperature to obtain a two-dimensional lamellar structure CuO.

[0047] Example 2

[0048] A method for preparing a two-dimensional layered CuO structure comprises the following steps:

[0049] The Cu-MOF prepared in Example 1 was placed in a muffle furnace and heated from 25°C to 400°C at a heating rate of 2°C / min, and kept at 400°C for 2 hours. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a two-dimensional lamellar structure CuO.

[0050] Example 3

[0051] A method for preparing a two-dimensional layered CuO structure comprises the following steps:

[0052] The Cu-MOF prepared in Example 1 was placed in a muffle furnace and heated from 25°C to 500°C at a heating rate of 2°C / min, and kept at 500°C for 2 hours. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a two-dimensional lamellar structure CuO.

[0053] Example 4

[0054] A method for preparing a two-dimensional layered CuO structure comprises the following steps:

[0055] The Cu-MOF prepared in Example 1 was placed in a muffle furnace and heated from 25°C to 600°C at a heating rate of 2°C / min, and kept at 600°C for 2 hours. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a two-dimensional lamellar structure CuO.

[0056] Example 5

[0057] A method for preparing a two-dimensional layered CuO structure comprises the following steps:

[0058] The Cu-MOF prepared in Example 1 was placed in a muffle furnace and heated from 25°C to 700°C at a heating rate of 2°C / min, and kept at 700°C for 2 hours. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a two-dimensional lamellar structure CuO.

[0059] Example 6

[0060] A method for preparing a two-dimensional layered CuO structure comprises the following steps:

[0061] The Cu-MOF prepared in Example 1 was placed in a muffle furnace and heated from 25°C to 800°C at a heating rate of 2°C / min, and kept at 800°C for 2 hours. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a two-dimensional lamellar structure CuO.

[0062] The XRD patterns of the two-dimensional (2D) sheet structure CuO prepared in Examples 1 to 6 and the Cu-MOF prepared in Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that no oxidation occurs at 200°C (the ligand decomposition temperature has not been reached); as the oxidation temperature increases (400°C to 800°C), the (111) crystal plane of CuO has a preferential growth trend. Under the temperature conditions of 700°C and 800°C, the (111) crystal plane of CuO tends to be stable.

[0063] The SEM image of Cu-MOF prepared in Example 1 is as follows Figure 2 As shown. Figure 2 It can be seen that Cu-MOF is in the form of multi-layer stacking, with a smooth surface and no obvious particles, indicating that Cu-MOF was successfully prepared.

[0064] The SEM images of the two-dimensional (2D) layered CuO prepared in Examples 1 to 6 are as follows: Figure 3 As shown. Figure 3 It can be seen that as the oxidation temperature increases, the particles continue to grow and the layered structure gradually disappears. However, the layered structure is still retained and the overall structure does not collapse, indicating that there is a strong interaction between the crystal planes of CuO (not 111 planes).

[0065] Application Examples

[0066] 5 mg of the two-dimensional sheet structure CuO prepared in Examples 2 to 6 were respectively dispersed in 970 μL of acetone and 30 μL of Naifion mixed solution, and subjected to cold water ultrasonic treatment for 2 h to obtain a mixed solution;

[0067] The mixed solution was dripped onto a hydrophobic carbon paper (size 3 cm × 1.5 cm), and the loading amount of CuO on the hydrophobic carbon paper was 1 mg / cm 2 , obtaining a working electrode;

[0068] Electrochemical reduction of CO2 is carried out in a gas diffusion electrolyzer. The specific process is:

[0069] The gas diffusion electrolyzer consists of four parts: ion exchange membrane (Nafion 117 membrane), anode chamber, cathode chamber and flowing CO2 gas chamber;

[0070] The electrolyte (1M KOH) was refluxed using a peristaltic pump, wherein the side of the working electrode prepared above that was loaded with CuO was in contact with the electrolyte, and the side of the working electrode that was not loaded with CuO was in communication with the gas chamber, the CO2 flow rate was 20 mL / min, the electrolyte flow rate was 7 mL / min, Ag / AgCl was used as a reference electrode, and a platinum sheet was used as a counter electrode;

[0071] The catalyst (working electrode loaded with two-dimensional sheet structure CuO) was pretreated by linear sweep voltammetry (LSV) for 10 cycles (scan rate of 50mV / s) in the voltage window range of 0 to -2V. After the structural evolution stabilized, cyclic voltammetry (CV) and impedance spectroscopy (EIS) were performed in the non-Faraday potential window at different scan rates to estimate the electrochemically active surface area ECSAs. The formula E RHE =E Ag / AgCl +0.197V+0.0591pH, all potentials measured with Ag / AgCl as reference were converted to relative reversible hydrogen electrode potentials (RHE).

[0072] Gas product analysis: Gas chromatograph GC, flame ionization detector FID and thermal conductivity detector TCD are used to detect gas products online.

[0073] FEgas=nvFN / VI;

[0074] Where n is the amount of gas measured by gas chromatography, v is the CO2 gas flow rate of 20sccm, F is the Faraday constant (96485C / mol), N is the number of transferred electrons to produce gas product molecules, V is the volume of 1 mol of gas at 298.15K and 101.325kPa (24.45L), and I is the average current mA.

[0075] Liquid product analysis: 0.5 mL of liquid product was mixed with 100 uL D2O (containing 25 ppm of DMSO) and analyzed using a liquid nuclear magnetic resonance spectrometer. The Faraday efficiency of the liquid product can be calculated as:

[0076] FE liquid =nFN / Q;

[0077] Where n is the molar amount of the liquid product, F is the Faraday constant (96485C / mol), N is the number of transferred electrons generated by the liquid product molecules, and Q is the total input charge, which can be directly read from the electrochemical workstation.

[0078] The CO2RR performance of the two-dimensional (2D) layered CuO prepared in Examples 2 to 6 is shown in FIG. Figure 4 As shown. Figure 4 It can be seen that with the increase of temperature, the (111) crystal plane of CuO has a preferential growth trend. The two-dimensional (2D) lamellar structure CuO has the highest ethylene selectivity of ~65% at 600°C, which may come from the preferential selectivity of the CuO (111) crystal plane. Under the temperature conditions of 700°C and 800°C, although it has the optimal CuO (111) crystal plane, due to the continuous increase of CuO particles, the specific surface area of ​​its overall two-dimensional (2D) lamellar structure decreases, and the adsorption of carbon dioxide is weakened. This leads to a decrease in its ethylene selectivity.

[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a two-dimensional layered CuO structure, characterized in that: The following steps are involved: The terephthalic acid, the first organic solvent, the second organic solvent and Cu(NO3)2·3H2O are mixed and subjected to a hydrothermal reaction to obtain Cu-MOF; Cu-MOF is calcined to obtain two-dimensional layered structure CuO.

2. The method for preparing the two-dimensional layered CuO according to claim 1, characterized in that: The usage ratio of the terephthalic acid, the first organic solvent and the second organic solvent is 30-50 mg: 1-6 mL: 0.5-3 mL; The first organic solvent is N,N-dimethylformamide or dimethyl sulfoxide; The second organic solvent is ethanol, methanol, propanol or isopropanol.

3. The method for preparing the two-dimensional layered CuO according to claim 2, characterized in that: The mass ratio of terephthalic acid to Cu(NO3)2·3H2O is 3-5:2-4.

4. The method for preparing the two-dimensional layered CuO according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 4-8 hours.

5. The method for preparing the two-dimensional layered CuO according to claim 3 or 4, characterized in that: The calcination conditions are as follows: the initial temperature is 20-30°C, the final temperature is 200-800°C, the heating rate to the final temperature is 1-5°C / min, and the insulation time at the final temperature is 1-5h.

6. The two-dimensional lamellar structure CuO obtained by the preparation method of the two-dimensional lamellar structure CuO according to any one of claims 1 to 5.

7. Use of the two-dimensional layer structure CuO as claimed in claim 6 in electrocatalytic CO2 reduction to produce ethylene.

Citation Information

Patent Citations

  • Graphene-loaded lamellar cupric oxide composite material and hydro-thermal synthesis method thereof

    CN102765715A

  • Bimetallic organic framework nano flowers, derivative thereof as well as preparation methods and applications of nano flowers and derivative

    CN110270333A

  • Preparation method and application of CuO nanosheet / g-C3N4 nanosheet heterojunction composite material

    CN111659434A

  • Preparation method of two-dimensional copper oxide nanosheet material

    CN115710009A

  • Porous CuO layered nanostructure electrode material and preparation method thereof

    CN116730380A